(3eLehYI aj GdcjejGAs - (3GdMcje gQeS , gQeS GdgQGeSIs
(3ChdgG (B:s
(3Gddhf LfS ef GdCLfGS hEfeG LfS GdCLfGS dCfg jbSe GdSOGO hGdjGV hGdMeQI hGdUaQI s
(3BNQgG (B:s
(3hcPdc CjVkG fhQ GdTeS HfhQ GdHUQ aMOKfG ef HjfgeG fhQ efHSW aCUGHg GdLSO JeJ GdebGdI HMeO Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGefs
(3Jdi GdeNWhW GdYOjO ef GdahGFO ai GdUfYIs
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdcjejGA h GdWHjYjGJs